Diagnostic tests for progestogen hypersensitivity - Alonso Bello, César Daniel; González Guzmán, Otto Pavel; Moncayo Coello, Carol Vivian; Rojo Gutiérrez, María Isabel; Castrejón Vázquez, María Isabel (Frontiers in Allergy, 2024)
Progesterone is an endogenous hormone, produced by the adrenal cortex, the gonads and in women, its source is the corpus luteum. Progesterone is produced in the late phase of the menstrual cycle, when implantation of the zygote does not occur, the corpus luteum involutes and the release of progesterone is suppressed, thus initiating menstruation. Progestogen Hypersensitivity were initially identified as hormone allergy and were related to endogenous reactions to hormones and alteration of ovarian function. Skin manifestations such as dermatitis or urticaria were initially reported and described as progesterone autoimmune dermatitis, although the immune-mediated mechanism was not clear. Currently there is no standardization for in vivo or in vitro tests for Progestogen Hypersensitivity diagnosis. In this review, we will address the different diagnostic methods of this disease.